1990
DOI: 10.5511/plantbiotechnology1984.7.187
|View full text |Cite
|
Sign up to set email alerts
|

Growth and flowering of in vitro-propagated Lilium auratum bulbs in soil.

Abstract: The cultivation in soil of bulblets of Lilium auratum propagated by tissue culture was investigated. In vitro-produced bulblets of L. auratum grew well in soil and required 3 growing seasons for normal flowering. Flowering time and flower quality were uniform and the plants revealed no virus symptoms. Abnormal flowers (four br five tepals) were observed when the bulbs were less than 15 g, while all flowers were norma when the bulbs were over 15g. Flower opened within a week and the size distribution of flower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…The applied increase in the external sucrose concentration thus leads to a considerable rise in the external sucrose level which would not argue for a signal function. The positive effect of sucrose on stem formation in lily has been described earlier (Takayama et al 1982).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The applied increase in the external sucrose concentration thus leads to a considerable rise in the external sucrose level which would not argue for a signal function. The positive effect of sucrose on stem formation in lily has been described earlier (Takayama et al 1982).…”
Section: Discussionsupporting
confidence: 65%
“…Lily bulblets regenerating in vitro on scale segments may undergo the vegetative phase change as they may form stems after planting in soil (Takayama et al 1982). This opens the possibility to study the transition from juvenile to adult in a reduced period of development under controlled culture conditions, and without interference of plant parts apart from the explant.…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of increased bulblet size might be offset by adverse effects on dormancy as a relationship between sucrose supply and bulblet dormancy has been demonstrated for Lilium species (Takayama et al, 1982, Aguettaz et al, 1990. Squires et al (1991) reported prolongation of Narcissus bulblet dormancy when sucrose supply was increased.…”
Section: Discussionmentioning
confidence: 94%
“…Considering that the bulb size is a characteristic that is directly proportional to the weight, Takayama and Ohkawa (1990) also observed that the bigger the bulb weight, the greater the length of the stem for Lilium auratum. Asker (2012) showed the importance of the presence of lily bulbs during cultivation, since the removal of bulbs in different weeks after planting seemed to reduce plant growth.…”
Section: Plant Heightmentioning
confidence: 99%